2016
DOI: 10.1016/j.indcrop.2016.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous synergistic microwave–ultrasonic extraction and hydrolysis for preparation of trans-resveratrol in tree peony seed oil-extracted residues using imidazolium-based ionic liquid

Abstract: a b s t r a c tImidazolium-based ionic liquid-based microwave-ultrasonic synergistic simultaneous extraction and hydrolysis (IMUSEH) method was developed to obtain trans-resveratrol from tree peony (Paeonia rockii (S.G. Haw & Lauener) T. Hong & J.J. Li) seed oil-extracted residues, in which the basic ionic liquid aqueous solution was used for extraction and transformation of trans-resveratrol glycosides to free transresveratrol. Through comparison, 1-butyl-3-methylimidazolium imidazolide ([C 4 C 1 im]Im) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 64 publications
(57 reference statements)
0
33
0
Order By: Relevance
“…As a popular traditional ornamental plant, Paeonia ostii T. Hong & J. X. Zhang (Paeoniaceae) has been widely cultivated in China for more than 2000 years due to its beautiful ornamental flowers and medicinal use of its roots . Cultivated tree peonies have nearly more than 1000 cultivars derived from a few traditional ones with particular characters in different regions after several thousand years of breeding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a popular traditional ornamental plant, Paeonia ostii T. Hong & J. X. Zhang (Paeoniaceae) has been widely cultivated in China for more than 2000 years due to its beautiful ornamental flowers and medicinal use of its roots . Cultivated tree peonies have nearly more than 1000 cultivars derived from a few traditional ones with particular characters in different regions after several thousand years of breeding.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the city of Luoyang, Heze, Linxia, Bozhou and Xiangyang are the most important peony cultivation areas in China. Oil tree peony is a new type of tree peony cultivar where the seed kernels can be used for the preparation of edible oil, and P. ostii or P. rockii are the only two oil peony cultivars authorised by the Ministry of Health of the People's Republic of China in March 2011 . The plantation area of oil tree peony is very large at present due to the high oil content (varies from 24.12% to 37.83%) in peony seed kernels and the high unsaturated fatty acid content (more than 90%) in peony seed oil …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that solvent extracts and essential oils of P. suffruticosa flower buds possess potential antimicrobial activities against some of the common food-borne bacterial pathogens (Han and Bhat, 2014;Wang et al, 2004). In the another study, the trans-Resveratrol, 3,5,4′-trihydroxy-trans-stilbene, a stilbenoid compound, known for its therapeutic and pharmacological activities was extracted from peony seeds by the imidazolium-based ionic liquidbased microwave-ultrasonic synergistic simultaneous extraction and hydrolysis methods (Chen et al, 2016). Also, peony seeds are the source of polysaccharides and four types of polysaccharides sequentially extracted from peony seed dregs have displayed strong antioxidant activities in a recent study (Shi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, severe water deficiency stress can limit the cultivation area, lead to smaller leaves and flowers, inhibit the synthesis of organic substances and flower pigments, and reduce the ornamental value and seed yield of tree peony (Li et al., ). Recent studies, however, have mainly focused on oil extraction (Chen et al., , b; Cui et al., ; Han et al., ). In addition, efficient protocols for the micropropagation of tree peony and the effects of different medium compositions and exogenous hormones on the browning of tree peony callus in tissue culture were recently investigated (Wen et al., ; Zhou et al., ).…”
mentioning
confidence: 99%